Appendix F - Architectual Drawings- Lakedell Front Entryway Upgrade ... - Van Someren, Trevor (University of Alberta Library, 2016)
Using autobiographical narratives reflecting on personal growth experiences with wisdom traditions, this project examines how a school community can engage with wisdom traditions as a positive method of decolonization. The project reflects on how purposeful leadership is used to embed wisdom traditions into the day to day climate of a school community. It reflects on wisdom traditions including the use of Elders, the use of story, ceremony, and smudging. Some key findings were that since schools played a key role in colonization in particular through the use of residential schools and the denying of First Nations, Metis and Inuit cultural representation within educational institutions. As such educational institutions need to change as opposed to expecting First Nations, Metis, and Inuit people to change. Educational institutions need to reach out to families to invite involvement in their school community in relevant and meaningful ways while honouring traditional protocols when applicable. Further findings ...